Diseño de una estrategia para la exportación de joyas en filigranas hacia el mercado de Colombia desde el cantón Chordeleg, provincia del Azuay - Sucuzhañay Amendaño, Mery Verónica (2015)
Chordeleg, a small town an hour east of Cuenca, Azuay Province, is famous for its fine filigree jewelry which includes: necklaces, rings, bracelets and earrings of excellent quality; over time, the jewelry became a symbol of the town, where more than 70 % of people are jewelers, real artists. Today, working with fine threads of gold and silver but stones like emeralds, diamonds, opals, aquamarines, pinks France, topaz and pearls are also used to give a touch of elegance to enhance and different models. Artisans canton Chordeleg Azuay province, are a group of producers and traders, engaged in the production of jewelry filigree, where an analysis of the macro and micro environment to determine their strengths, weaknesses, opportunities and threats are made, and encourage the continued development of the production and marketing of jewelry. In this research, we propose to local artisans, developing strategies to encourage the export of its products, based on research of the current market situation and trade, understanding the current situation of the artisans is poor, its economy or performance of its sales have been profitable, but is presented with the option to increase the same inroads in the export of gems which will only bring more benefits and development for your business. The project implementation requires training to artisans, since lack of knowledge about the raid on exports of its products makes trading remains at the national level, so the proposed solution is that the producer and marketer will offer itself craft training you need in that ignorance is not an issue when it comes to internationalize their products, and choose to accept the proposal and implement it.